1992
DOI: 10.1159/000288581
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Conjugate Lateral Eye Movements and Alexithymia

Abstract: The relationship between conjugate lateral eye movements (CLEMs) and alexithymia was investigated in a group of 60 (23 male and 37 female) right-handed university students. Subjects completed the Toronto Alexithymia Scale (TAS), the Schalling-Sifneos Personality Scale, and the Basic Personality Inventory, which measures 12 basic dimensions of personality and psychopathology. CLEMs were recorded while subjects were asked 20 general knowledge questions that have no tendency to elicit eye movements predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
3
12
0
1
Order By: Relevance
“…Two behavioral studies of conjugate lateral eye movements (CLEMs) addressed the relation of alexithymia to RH activation [51, 52]. CLEMs refer to the eye movements people make as they begin to think about something.…”
Section: Behavioral Studies Of the Rh Deficit Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Two behavioral studies of conjugate lateral eye movements (CLEMs) addressed the relation of alexithymia to RH activation [51, 52]. CLEMs refer to the eye movements people make as they begin to think about something.…”
Section: Behavioral Studies Of the Rh Deficit Modelmentioning
confidence: 99%
“…To address the methodological weaknesses of the study by Cole and Bakan [51], Parker et al [52]replicated it using the TAS in addition to the SSPS, otherwise using the exact same methodology. Subjects were 60 right-handed university students.…”
Section: Behavioral Studies Of the Rh Deficit Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating conjugate lateral eye movements found conflicting results on the right hemisphere activity in alexithymia [19, 20]. In a PET study, Lane et al [21]found reduced activation of the right anterior cingulate cortex in subjects with a low level of emotional awareness during an emotional stimulation paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…ИсслСдования ΠΏΠΎ-ΠΊΠ°Π·Ρ‹Π²Π°ΡŽΡ‚ ΡΠ²Π½ΡƒΡŽ связь АВ со спСциализациСй ΠΏΠΎΠ»ΡƒΡˆΠ°Ρ€ΠΈΠΉ ΠΌΠΎΠ·Π³Π° ΠΈ Π² ΠΎΡ‡Π΅Ρ€Π΅Π΄Π½ΠΎΠΉ Ρ€Π°Π· ΠΏΠΎΠ΄Ρ‚Π²Π΅Ρ€ΠΆΠ΄Π°ΡŽΡ‚ полоТСния Ρ‚Π΅ΠΎΡ€ΠΈΠΈ систСмной динамичСской Π»ΠΎΠΊΠ°Π»ΠΈΠ·Π°Ρ†ΠΈΠΈ Π²Ρ‹ΡΡˆΠΈΡ… психичС-ских Ρ„ΡƒΠ½ΠΊΡ†ΠΈΠΉ [35].…”
unclassified